Perencanaan dan Pengendalian Persediaan Obat Terlaris Pada Apotek Zakky - Minhatin Nisaatus Sholikhah; Yusnia Megasari; Mohammad Syaiful Pradana (UJMC (Unisda Journal of Mathematics and Computer Science), 2022)
This study aims to analyze the control of drug supplies at Zakky 3 pharmacies from December 2020 to January 2021. The data used are primary data and secondary data. Data collection methods used in this study are observation, interviews, and documentation. For drug procurement planning, in this study an analysis of the investment value was conducted to determine which drugs were included in groups A, B, and C. Furthermore, the Economic Order Quantity (EOQ) calculation was carried out to determine the number of economic orders, as well as the calculation of Reorder Point (ROP) for know the point of reordering drugs for the period of 2021. The results of the analysis show that in the ABC analysis of investments, 500 types of drugs are included in group A or 31% of all drugs, absorbing 78% of investment, group B with 496 types of drugs or 31% % of all drugs, absorbing 16 %% of investment. Meanwhile, group C with 612 types of drugs or 38%% of all drug item drugs only absorbed 6% of the investment. Also obtained are the results of EOQ and ROP calculations for the period of 2021. This calculation is useful for helping pharmacies in drug procurement so that there is a balance between service levels and costs.